Enantioselective Cobalt-Catalyzed C–H Functionalization - Xu, Weiwei; Ye, Mengchun (Synthesis, 2022)
Co-catalyzed C–H functionalization has received great attention due to the high earth abundance, low biotoxicity, and unique reactivity of cobalt; enantioselective control of these reactions has been a formidable challenge. Various efficient strategies have recently been developed for enantioselective Co-catalyzed C–H functionalization, but there is no topical review of this field. Herein, we give a detailed summary of this rapidly growing field, highlighting critical progress, current challenges, and future trends.1 Introduction2 Enantioselective C–H Functionalization via Low-Valent Co Catalysis2.1 Chiral Diphosphines for Enantioselective Control2.2 Chiral Monophosphines or N-Heterocyclic Carbenes for Enantioselective Control3 Enantioselective C–H Functionalization via High-Valent Co Catalysis3.1 Chiral Acids for Enantioselective Control3.2 Chiral Cp Ligands for Enantioselective Control4 Conclusions and Outlook
Keywords: enantioselective; cobalt catalysis; C–H functionalization; chiral acid; chiral cyclopentadienyl ligand